Federico García Lorca : el 75 aniversario de su muerte - Katona, Eszter (Acta Hispanica, 2011)
The anniversary of Federico Garría Lorca’s death and the outbreak of the Spanish Civil War is closely intertwined in the Spanish public awareness. The poet’s birth date is equally an important date in the his toy of the Iberian nation, as Spain has lost its last colonies in 1898. Besides these two memorable dates, we also have to highlight 2007, when the Historical Memory Law (Ley de Memoria Histórica) was enacted, aiming to rehabilitate the victims of the Civil War and the Franco regime. This measure has launched such an avalanche on Spanish public life, that affected almost all the society in some way. The family of Garcia Lorca also had to take a commitment as the resting place of their world-famous relative was still unknown. In addition to the identification of the body of the dead poet, Lorca’s homosexuality is a constant topic in literary and historical arríes. Today, Spanish society accepts the sexual orientation of the poet, but it remains disputed whether it had a real effec t on Lorca’s poetry. Lorca’s Hungarian popularity began in 1947 when Gypsy Ballads was issued then the premier of Bernarda in 1955, and has remained unbroken ever since. In connection with this year’s anniversary, this study aims to present these three topics — the location of Lorca’s resting place, Lorca’s homosexuality, Lorca’s reception in Hungary.